The teaching efficacy among trainee teachers in the classroom environment. - Jamian, Abdul Rasid; Othman, Shamsuddin; Baharom, Rashidah (2013)
The objective of the study is to assess the teaching efficacy among trainee teachers in the classroom environment in their teaching practice. The specific objective is to determine the trainee teachers in pedagogical aspects in classroom. Findings indicate that a majority of the respondents have a high level of confidence with their efficacy in terms of student engagement (Mean: 3.97, S.D: 0.29), instructional strategies (Mean: 3.93, S.D: 0.38), classroom management (Mean: 3.90, S.D: 0.32) and computer aided teaching in classroom (Mean: 3.83, S.D: 0.57). The conclusion is trainee teachers in term of student engagement, instructional strategies, classroom management and information communication technology is high.